Magnetic reconnection as a mechanism to produce multiple protonpopulations and beams locally in the solar wind - Lavraud,B; Kieokaew,R; Fargette,N; Louarn,P; Fedorov,A; André,N; Fruit,G; Génot,V; Réville,V; Rouillard,AP; Plotnikov,I; Penou,E; et al. (Journal of Astrophysics and Astronomy, 2021)
Context. Spacecraft observations early revealed frequent multiple protonpopulations in the solar wind. Decades of research on their origin have focusedon processes such as magnetic reconnection in the low corona and wave-particleinteractions in the corona and locally in the solar wind.Aims.This study aimsto highlight that multiple proton populations and beams are also produced bymagnetic reconnection occurring locally in the solar wind. Methods. We use highresolution Solar Orbiter proton velocity distribution function measurements,complemented by electron and magnetic field data, to analyze the association ofmultiple proton populations and beams with magnetic reconnection during aperiod of slow Alfv\'enic solar wind on 16 July 2020. Results. At least 6reconnecting current sheets with associated multiple proton populations andbeams, including a case of magnetic reconnection at a switchback boundary, arefound during this day. This represents 2% of the measured distributionfunctions. We discuss how this proportion may be underestimated, and how it maydepend on solar wind type and distance from the Sun. Conclusions. Althoughsuggesting a likely small contribution, but which remains to be quantitativelyassessed, Solar Orbiter observations show that magnetic reconnection must beconsidered as one of the mechanisms that produce multiple proton populationsand beams locally in the solar wind.